Tabula Imaginarium - An Ipad application for aiding a spatially separated tabletop role-playing game. - Johansson, Jonathan; Lundberg, Peter (My University, 2012)
This report describes the conceptualization and development of an Ipad application, called Tabula Imaginarium, with the purpose of aiding a player of a tabletop role-playing game that is spatially separated from the other participants. Guided by the main design goal of being an application that should be a natural part of the role-playing activity, even if a player is not spatially separated from the other participants, Tabula Imaginarium presents a way to easily and quickly draw maps on the fly during a role-playing session, and live-time synchronization of these maps between applications on different Ipads. In order to do this, it contains different drawing features as well as placement and movement of objects and character tokens. The report summarizes the features of similar applications, such as Virtual Tabletop applications for the PC and map-drawing applications for Ipad. It also presents theory that describes the activity of tabletop role-playing in depth. In the conceptualization part the report describes brainstorming sessions as well as application of theory in order to pinpoint parts of the tabletop role-playing activity that is important to transfer to the Ipad device. This can be seen to mainly focus on the immersion of the spatially separated player. The iterative nature of development is also depicted in its five cycles of design, implementation, user testing and analysis, and ended by its final test with remote test persons. In the last parts of the report, the features of Tabula Imaginarium are described in detail, while presenting suggestions of future improvements that could further aid in immersing a spatially separated player.
Keywords: Datavetenskap (datalogi); Computer Science